Analisis Pemanfaatan Sampah Plastik (Recycle) sebagai Upaya Pengendalian Lingkungan di Gampong Peurada, Banda Aceh - Syarifah Farissi Hamama; Maulida Maulida; Irma Aryani (Jurnal Dedikasi Pendidikan, 2024)
Plastic waste is a major problem in environmental pollution. This is influenced by the nature of plastic waste, which is difficult to decompose. Plastic is very useful and has become an integral part of people's lives. However, the use of single-use plastic products has caused various negative impacts on the environment. This plastic waste problem is also experienced by residents of Gampong Peurada, Banda Aceh. This is due to the high use of buildings and housing in the area, such as boarding houses and rental houses. Where the lifestyle and level of consumption of plastic by residents of boarding houses and rental houses are very high. This research was conducted to obtain data related to the processing of plastic waste carried out by the residents of Gampong Peurada. Data collection was carried out qualitatively through interviews and observations. The data were analysed descriptively and presented in the form of tables and figures. The results of the research show that the processing of plastic waste carried out by the people of Gampong Peurada produces shopping bags, wallets, flower decorations, and accessories in the form of brooches and key chains